Indexing of Colombian psychology journals in Spanish scientific databases: an exploratory study (2021)
An exploratory work that analyzes the relevance of the principal Colombian psychology journals [those that are indexed in the most important national (Publindex) and international (Web of Science and Scopus) indicators], depending on the figures provided by two Spanish scientific databases (CIRC and MIAR), widely used in the bibliometric field is presented in the following document. By means of a Spearman correlation analysis between these three elements and Google Scholar H5 index the results show the existence of a strong correlation between Publindex and H5 index (r = 0.86 / p = 0.001) no there being significant differences between Publindex and the European matrices. In addition, it can be considered that CIRC data matrix underestimates this type of publications in comparison with the other three meters and therefore we would not recommend the use of this last Spanish database to Colombian psychologists. © 2021,Universitas Psychologica. All Rights Reserved